2002
DOI: 10.1027//1016-9040.7.2.116
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Work Hours and Schedules on the Physical and Psychological Well-Being in Medical Practices

Abstract: In a random sample of just over 300 medical doctors and consultants throughout Germany, various job-related variables were assessed together with sociodemographic data including time-related parameters of work, and specific categories of accidents (moving vehicle and work-related). Occupational stress was related to number of weekly working hours, duration of the lunch-break, as well as age. Moving vehicle accidents (MVAs) were significantly correlated with the incidence of work-related accidents during the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 21 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…13 Low levels of job satisfaction are closely related with poor mental health; this is a downward spiral: poor mental health has an adverse impact on patient care which in turn further upsets the physician. 6,7,9,12,14,16,18,[27][28][29][30] As a conclusion, primary health care physicians' job related negative emotional perceptions were associated with reactions in terms of stress, anxiety and depression, and further studies that focus on these issues in a qualitative manner are needed. Because primary health care physicians' job related affective well-being matter, they were serving as gate-keepers for the health of the whole nation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Low levels of job satisfaction are closely related with poor mental health; this is a downward spiral: poor mental health has an adverse impact on patient care which in turn further upsets the physician. 6,7,9,12,14,16,18,[27][28][29][30] As a conclusion, primary health care physicians' job related negative emotional perceptions were associated with reactions in terms of stress, anxiety and depression, and further studies that focus on these issues in a qualitative manner are needed. Because primary health care physicians' job related affective well-being matter, they were serving as gate-keepers for the health of the whole nation.…”
Section: Discussionmentioning
confidence: 99%
“…4 Studies focused on primary health care physicians mostly assessed the sources of stress and predictors of job satisfaction among GPs, and indicated how job stress affects levels of job satisfaction. [5][6][7][8][9][10][11] Time pressure, interruptions, practice administration, dealing with difficult patients and work/home conflict were found as the main sources of stress for GPs. [12][13][14][15] In Australia, 68% of GPs that were questioned were satisfied with their job; 16 in the US, the satisfaction level increased to 82% among primary care physicians.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of temporal parameters and their influence on the performance and medical errors has been addressed in the literature during the last twenty years (the more recent being the ones by Kirckaldy et al, 1997Kirckaldy et al, , 2002Trimpop et al, 2000). Sleep deprivation related to demanding work schedules has also been linked to poorer work performance in JHDs (Spurgeon and Harrington, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…A survey of radiologists in Saudi Arabia found that infrequent break taking was predictive of digital eye strain,38 while in the UK,39 doctors reported lack of breaks as the most common barrier to healthy eating. Two studies (in Egypt and Germany)40 41 found that fewer breaks correlated with, or were predictors of, higher stress levels, whereas a survey of physicians in private practice42 found that break taking negatively correlated with work-home conflict and indirectly correlated with emotional exhaustion. However, a small survey of 46 Tunisian anaesthetists of varying grades43 found no association between break-taking behaviours and levels of burnout.…”
Section: Resultsmentioning
confidence: 99%
“…As study design and break types under investigation varied markedly, they are described here by topic and data type to aid clarity, including quantitative studies of standard 30 min breaks, 24 25 sleep-related interventions (naps), 26 27 yoga and mindfulness interventions, [28][29][30][31] microbreaks in surgery, [32][33][34][35] other microbreak interventions, 36 37 surveys [38][39][40][41][42][43][44] and cohort studies. [45][46][47][48] Qualitative data are grouped into qualitative evaluations of interventions 49 50 and other qualitative studies, [51][52][53][54] and a single German sequential mixed-method study investigating the impact of breaks on opportunities for physicians to share (or hide) ignorance 55 (see online supplemental table 4).…”
Section: Impact Of Breaks On Well-being and Performance Outcome Measuresmentioning
confidence: 99%